The features of enamel histoarchitectonics in human permanent molar teeth at the occlusal surface of the crown and at the sites of transition of its approximal surfaces to vestibular and lingual ones - О. І. Тіrоn; V. Ye. Breus; А. V. Тоdorovа (Zaporožskij Medicinskij Žurnal)
Objective. The aim of this study is to characterize the dimensional orientation of enamel rods in human permanent molar tooth at the sites of transition from its aproximal surfaces to the vestibular and oral ones, and also at the occlusal surface.